The Effect Of Junggling-Forehand Combination Training On The Accuracy Of Table Tennis Forehand In PTM Central Boyolali Athletes - Miko, Agung; Pungki Indarto (Jurnal Pendidikan Jasmani (JPJ), 2023)
The Whether you can play table tennis or not depends on whether you have basic skills or not. One of the basic techniques that still has many obstacles is the forehand. Forehand skills at PTM Central, the ball often gets caught in the net and his shots are often on target. Several factors that are thought to affect the accuracy of forehand strokes are poor hand-eye coordination. Junggling combined with Forehand precision has never been scientifically measured. Using a quantitative type with One-Grub Pretest-Posttest Research Design Research which took place at PTM Central Boyolali which was carried out for 1 month, from June 17 to July 17. The population itself is 20 athletes and the sample is 15 athletes using purposive sampling. Observations, tests, and documentation used for data collection techniques. For the data analysis section itself using inferential statistical tests and descriptive statistical tests. The results of the pretest and posttest were analyzed using statistical prerequisite tests and hypothesis testing. There is an effect of combined junggling-forehand exercise on the accuracy of the forehand in PTM Central Boyolali athletes. The forehand accuracy in PTM Central Boyolali athletes increased from the average pretest 63.27 and posttest 73.07. There was a significant difference between pretest and posttest with a significance value of 0.000 <0.05.